2010
DOI: 10.1371/journal.pone.0009267
|View full text |Cite
|
Sign up to set email alerts
|

Allyl Isothiocyanate that Induces GST and UGT Expression Confers Oxidative Stress Resistance on C. elegans, as Demonstrated by Nematode Biosensor

Abstract: BackgroundElectrophilic xenobiotics and endogenous products from oxidative stresses induce the glutathione S-transferases (GSTs), which form a large family within the phase II enzymes over both animal and plant kingdoms. The GSTs thus induced in turn detoxify these external as well as internal stresses. Because these stresses are often linked to ageing and damage to health, the induction of phase II enzymes without causing adverse effects would be beneficial in slowing down ageing and keeping healthy condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…elegans with life span extension often show enhanced resistance to thermal and oxidative stress [10], suggesting that worms fed the GD1 diet would also demonstrate stress resistance. Juglone is a quinone that imposes both oxidative and electrophilic stress [27,28]. Juglone penetrates the worm cuticle and has been used to select for oxidative stress-resistant mutants [29].…”
Section: Resultsmentioning
confidence: 99%
“…elegans with life span extension often show enhanced resistance to thermal and oxidative stress [10], suggesting that worms fed the GD1 diet would also demonstrate stress resistance. Juglone is a quinone that imposes both oxidative and electrophilic stress [27,28]. Juglone penetrates the worm cuticle and has been used to select for oxidative stress-resistant mutants [29].…”
Section: Resultsmentioning
confidence: 99%
“…The only enriched "Molecular Function" (MF) GO term found for this compartment was "transferase activity, transferring hexosyl groups" (GO:0016758; p Ļ­ 1.5 Ļ« 10 ĻŖ5 ; Table II), an activity common among genes highly or exclusively expressed in the nematode intestine, for a variety of purposes including maintaining bacterial flora, producing mucin and modulating fat storage (4). Interpro domain enrichment testing showed that "UDP-glucuronosyl/UDP-glucosyltransferase" domains were the most significantly enriched among IIM proteins (IPR002213; p Ļ­ 3.3 Ļ« 10 ĻŖ4 ; Table III); UDP-glycosyltransferases are found in all living organisms, and in C. elegans they are primarily responsible for the detoxification of foreign compounds (65,66). The IIM proteins were also enriched for many ABC transporter domain-containing proteins (Table III) that affect the absorption, distribution, and elimination of xenobiotics, including known anthelmintic drugs (67,68).…”
Section: Functional Enrichment Analyses Reveal Known and Novel Functimentioning
confidence: 99%
“…Differential interference contrast and high-magnification fluorescent images were taken of worms with an Olympus BX60 microscope. Fluorescence was quantified from the photomicrographs with a nematode image analyzer FL (v1.0.0.1) as described previously (http://www.vision .cs.chubu.ac.jp/fl1001/ [33]). …”
Section: Yeast Assaysmentioning
confidence: 99%